Progress and challenge of amorphous catalysts for electrochemical water splitting - Zhou, Yao (2021)
Electrochemical water splitting has been regarded a promising technology to provide a mobile and sustainable energy supply in the form of hydrogen fuel. The key to further development towards industrial application lies in high-efficiency and low-cost electrocatalysts. In recent years, new attention has been paid to amorphous electrocatalysts, which have short-range atomic ordering instead of translational periodicity. The structural flexibility and rich defects associated with amorphous catalyst materials offer enormous opportunities for electrochemical water splitting. In this Perspective, we elaborate on recent studies of amorphous electrocatalysts for electrochemical water splitting. Our discussion covers the diverse amorphization strategies, the positive role of structural flexibility and defects in enriching active sites, as well as challenges in the characterization of local geometry and in improving electrochemical stability. Finally, we conclude with prospective remarks for future development in amorphous electrocatalyst materials for electrochemical water splitting.